Adenosquamous carcinoma coexisting with intraductal papillary mucinous neoplasm of the pancreas: a case report - Hirozumi Sawai; Yuka Kiriyama; Hiromasa Kuzuya; Yoshiaki Fujii; Shuhei Ueno; Shuji Koide; Masaaki Kurimoto; Kenji Yamao; Yoichi Matsuo; Mamoru Morimoto; Hajime Koide; Atsushi Kamiya (Journal of Medical Case Reports, 2023)
Abstract Background Adenosquamous carcinoma of the pancreas is a rare variant, with a worse prognosis than pancreatic ductal adenocarcinoma; moreover, it has characteristic clinical and histopathological features. Studies have mentioned the differentiation of intraductal papillary mucinous neoplasms into mucinous/tubular adenocarcinomas; however, their transdifferentiation into adenosquamous carcinoma remains unclear. Case presentation An 80-year-old Japanese woman was referred to our hospital for further examination of multiple pancreatic cysts. Enhanced computed tomography after close follow-up for 6 years revealed a new nodule with poor enhancement on the pancreatic body. Distal pancreatectomy and splenectomy were performed. Histopathological examination revealed an adenosquamous carcinoma with coexisting intraductal papillary mucinous neoplasms; moreover, the intraductal papillary mucinous neoplasms lacked continuity with the adenosquamous carcinoma. Immunohistochemical analysis revealed squamous cell carcinoma and differentiation from adenocarcinoma to squamous cell carcinoma. Gene mutation analysis revealed KRAS G12D and KRAS G12R mutations in adenosquamous carcinoma components and intraductal papillary mucinous neoplasm lesions, respectively, with none showing the mutation of GNAS codon 201. The final histopathological diagnosis was adenosquamous carcinoma with coexisting intraductal papillary mucinous neoplasms of the pancreas. Conclusions This is the rare case of adenosquamous carcinoma with coexisting intraductal papillary mucinous neoplasms of the pancreas. To investigate the underlying transdifferentiation pathway of intraductal papillary mucinous neoplasms into this rare subtype of pancreatic cancer, we explored gene mutation differences as a clinicopathological parameter.